Similarities and Differences of Health-promoting Leadership and Transformational Leadership - Anita Dunkl; Paul Jiménez; Simona Šarotar Žižek; Borut Milfelner; Wolfgang K. Kallus (Naše gospodarstvo/Our economy, 2015)
The concept of health-promoting leadership focuses on the interaction between the organization and the individual by identifying components able to positively influence employees’ working conditions. In the present study, the effects of health-promoting leadership and transformational leadership on the employees’ recovery–stress balance are investigated. In an online study, 212 Slovenian workers were asked about their perceptions of their direct supervisors and their work-related stress and recovery. The results showed that both leadership styles have a significant effect on employees’ recovery at the workplace, which mediated the relationship between leadership and work-related stress.